Keystone perforator island flap: a clinical summary of 28 melanoma cases - Felix Behan (Australasian Journal of Plastic Surgery)
**Background**: The keystone perforator island flap (KPIF) and its design variations developed as a clinical necessity for reconstructing large surgical defects. This article focuses on melanoma management in 28 cases taken from a series of up to 3,000 established over 20 years of clinical experience.